Application of simply and conveniently recycled IL-coated MOF composite material in treatment of antiviral drug pollutants in wastewater

Through the application of modified ionic liquid and metal organic frame composite materials, the problems of high cost, high energy consumption and low removal efficiency when treating antiviral drug contaminants in wastewater in the prior art are solved, efficient adsorption and catalytic degradation are achieved, and simple material recycling is provided.

CN119633757APending Publication Date: 2025-03-18TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311191572.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art has problems such as high equipment cost, high energy consumption, possible secondary pollution and low removal efficiency when treating antiviral drug contaminants in wastewater.

Method used

The modified ionic liquid (IL) and metal organic frame (MOF) composite materials are used to impart catalytic performance by adjusting the structure of IL, and the porosity and structural designability of MOF are used to enhance its adsorption and catalytic hydrolysis of antiviral drug contaminants.

Benefits of technology

This method can achieve efficient adsorption and catalytic degradation of antiviral drugs in the absence of external conditions (such as oxidants), significantly improve the removal rate of antiviral drugs in wastewater, and achieve simple recycling of materials through external stimulation methods.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to application of an ionic liquid and metal organic framework composite material with external stimuli response performance to removal of antiviral drug pollutants in wastewater. The composite material disclosed by the invention has adsorption and catalytic performances, the structure of the ionic liquid is adjusted to endow the composite material with high catalytic selectivity, and the structure of the metal organic framework is adjusted to endow the composite material with high adsorption selectivity, so that the purposes of in-situ adsorption and catalytic degradation of antiviral drug pollutants are achieved. After the reaction is finished, in-situ separation of the material can be realized through an external stimulation method for subsequent recycling, and the removal effect on antiviral drug pollutants can reach 92%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent and catalyst material application, and relates to the application of an ionic liquid-metal organic framework composite material in treating antiviral drug pollutants in wastewater. Background Art

[0002] In recent years, personal care products have been increasingly used in human and animal health care to improve quality of life and prolong life. Among them, antiviral drugs are a class of drugs that treat viral infections by preventing the growth of pathogens, but their frequent use and continuous accumulation in the environment have led to serious global environmental problems. Studies have shown that the presence of antiviral drug pollutants has been detected in surface water, groundwater, sewage and drinking water, and their content ranges from ng / L to mg / L. In addition, when an antiviral drug and the virus to be treated coexist in the same water body, susceptible organisms may acquire resistance, which may lead to the emergence of new antiviral resistance in the environment. Therefore, efficient treatment of these drugs has gradually become one of the research hotspots.

[0003] At present, treatment technologies such as ozone oxidation, photolysis, electrochemical advanced oxidation, photocatalysis, adsorption, activated sludge and membrane bioreactor are widely used. However, when the above technologies are used alone, there will be problems such as high equipment cost, high energy consumption, secondary pollution, additional harmful byproducts and inability to remove pollutants efficiently. Therefore, many scholars have adopted a multi-technical coupling method to efficiently and synergistically treat antiviral drug pollutants in sewage.

[0004] Patent CN111762978A uses UV / H2O2 combined with biological activated carbon technology to deeply treat pharmaceutical micropollutants in sewage. The removal rates of four pollutants, including carbamazepine, erythromycin, diclofenac and gemfibrozil, are all above 92%, and are about 10-50% higher than the removal rate of single UV / H2O2 technology, greatly reducing ecological risks; Patent CN107913673A uses metal organic framework materials as adsorbents and combines photocatalytic technology to remove organic pharmaceutical pollutants in water bodies. The removal rate can reach more than 98%, and the adsorbent can be reused many times without recycling to meet increasingly stringent water quality requirements.

[0005] Although the above methods can effectively remove pharmaceutical pollutants in water, most of the research still has problems such as high energy consumption, high cost and easy to cause secondary pollution. Metal Organic Framework (MOF) is a unique hybrid crystal material constructed by the self-assembly mechanism between metal ions or nodes and organic molecules. It is favored by adsorption technology due to its customizable porous structure and numerous active sites. It has the advantages of good thermal and chemical stability, high specific surface area and easy surface functionalization, and shows efficient removal ability in removing pollutants in water. According to the characteristics of the target analyte, it is a current research hotspot to modify the structure of MOF with functionalized reagents to obtain higher selectivity and adsorption capacity. Ionic liquid (IL) as a green organic reagent has been proven to have strong separation ability for a variety of organic compounds. After being flexibly fixed on different carriers, it has achieved excellent results in the fields of catalysis, extraction, adsorption, etc. By utilizing its structural designability, functionalizing its structure to improve its selectivity and combining it with the same functionalized MOF material, it is expected to show great potential in in situ adsorption-catalytic degradation.

[0006] The IL@MOF composite material proposed in the present invention is intended to simultaneously achieve adsorption and catalytic hydrolysis of antiviral drug pollutants in water without any external conditions (such as oxidants, etc.), so as to achieve the purpose of efficiently removing drug pollutants. Summary of the invention

[0007] The purpose of the present invention is to provide an IL@MOF composite material that can be used to simultaneously achieve adsorption and degradation of antiviral drug pollutants in water. The composite material is prepared by stirring and mixing separately modified IL and MOF materials according to a certain molar ratio. The simultaneous adsorption and catalytic degradation functions are achieved by adjusting the structure of the IL to give it catalytic properties and utilizing the porosity and structural designability of the MOF to enhance its adsorption selection function.

[0008] The modified IL-grafted MOF composite material proposed in the present invention is as follows:

[0009] 1) First, add 1-10g MOF into the modifier solution, seal it with plastic wrap and poke holes with a needle to allow the steam to condense and reflux;

[0010] 2) Oscillate in a constant temperature water bath at 50-150°C and an oscillation rate of 100-200 r / min for 1-12 hours. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind the modified MOF for later use.

[0011] 3) Dissolve 1-100g of biomass in the modifier solution and stir magnetically at room temperature for 1-24h. Then add the modified MOF and stir at room temperature for 1-12h. Centrifuge the resulting mixture several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a culture dish, dry it at 60-80℃ to constant weight, grind it for later use, and obtain the biomass-modified MOF compound;

[0012] 4) Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or a pyridine derivative or a quaternary ammonium salt derivative, react at a temperature range of 50-120° C. for 1-12 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, thereby obtaining compound 1;

[0013] 5) Add compound 1 into water and dissolve it. Add a heteropolyacid aqueous solution containing an equimolar amount of compound 1 dropwise during stirring. After the addition is complete, raise the temperature to 60-100° C. at a heating rate of 1-10° C. per minute and react for 1-10 hours. Finally, filter out the solid precipitate and send it to a vacuum drying oven for drying to obtain compound 2;

[0014] 6) Dissolve compound 2 in deionized water at 50-120° C., then mix it with metal chloride and add it, react at 90-120° C. for 1-6 hours to obtain an ionic liquid with temperature control function.

[0015] 7) Soak the modified MOF in deionized water for 24 hours and then centrifuge. Take 1-10g MOF and mix it with NaCl solution, stir it for 24-48 hours, dialyze it in deionized water until it is chlorine-free, and then dry it at 80℃-100℃. Then add excess IL to finally form a temperature-controlled IL@MOF composite material.

[0016] The materials in step 1) include iron-based materials, chromium-based materials, cobalt-based materials and other materials based on various metals; the modified solution is an acidic aqueous solution such as hydrochloric acid and sulfuric acid, an alkaline aqueous solution such as ammonia water, and an oxidizing modifier such as hydrogen peroxide and ozone;

[0017] The mass ratio of MOF to biomass in steps 1) and 3) is 1:1-1:10;

[0018] In the step 4), the volume ratio of 1,3-propane sultone to toluene is 0.1-1:1; the amount of N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative added is 0.013 mol-0.065 mol.

[0019] In step 6), the metal chloride is specifically AlCl 3 or CrCl 3; The molar ratio of metal chloride to compound 2 is 1:0.1-1.

[0020] In the step 7), the mass ratio of MOF to NaCl solution is 1:1-1:20, and the molar ratio of MOF to IL is 1:1-1:10.

[0021] The method of using the easily recyclable IL@MOF composite material prepared by the present invention to treat antiviral drugs in wastewater is as follows:

[0022] The prepared material is added to wastewater containing antiviral drugs, and then the system is placed in a water bath oscillator and oscillated at a rate of 100r / min-500r / min to allow the pollutants to be fully adsorbed by the composite material. The system is then placed at 60℃-120℃ for 1-24h, and the supernatant is taken for content determination after the reaction. The prepared material can be recovered by external stimulation method.

[0023] The antiviral drug pollutants are anti-HIV, anti-hepatitis, anti-influenza and anti-herpes virus and the like.

[0024] The method for using the easily recyclable IL@MOF composite material prepared by the present invention in treating antiviral drugs in wastewater is as follows: the prepared material is added to wastewater containing antiviral drugs, and then the system is placed in a water bath oscillator for oscillation at a rate of 100r / min-500r / min, so that the pollutants are fully adsorbed by the composite material. The system is then placed under conditions of 60°C-120°C for reaction for 1-24h, and after the reaction, the supernatant is taken for content determination, and the prepared material can be recovered by an external stimulation method.

[0025] The principle of the present invention is to utilize the porosity of the prepared material to adsorb the drug onto the surface of the material through hydrogen bond interaction, electrostatic effect, etc., and then utilize the catalytic properties of the prepared material to highly selectively degrade the drug to achieve the purpose of efficient removal.

[0026] The beneficial effects of the present invention are as follows: (1) The external stimulus responsiveness of the material solves the problem of difficult recovery of the material in homogeneous reactions and poor mass transfer in heterogeneous reactions; (2) It provides a new approach for the value-added utilization of ionic liquids and metal organic framework materials; (3) The combined use of ionic liquids and metal organic frameworks can simultaneously achieve the adsorption and catalytic degradation of antiviral drugs, significantly improving the removal rate of antiviral drugs in wastewater. DETAILED DESCRIPTION

[0027] Example 1

[0028] First, add 5g MOF to the modifier solution, seal it with plastic wrap and pierce it with a needle to condense the steam and reflux. Then oscillate it in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min for 8h. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind to obtain the modified MOF for use. Dissolve 20g biomass in the modifier solution and stir it magnetically at room temperature for 12h. Then add the modified MOF and stir it at room temperature for 10h. Centrifuge the obtained mixed solution several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a petri dish, dry it at 80℃ to constant weight, grind it for use, and obtain the biomass-modified MOF composite. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying to obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, then mixed with metal chloride and added, reacted at 90°C for 5 hours, and an ionic liquid with temperature control function is obtained. Soak MOF in deionized water for 24 hours and then centrifuge. Take 5gMOF and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. Then 2.5 g IL was added, finally forming a temperature-controlled and biomass-modified IL@MOF composite material.

[0029] 10 mg of functionalized IL@MOF composite material was weighed and added to 20 ml of 20 mg / L antiviral drug solution. The reaction system was then placed in a constant temperature shaker at 30 ° C and 190 rpm to fully promote the adsorption of antiviral drugs. The system was placed at 100 ° C for degradation reaction for 10 hours. All experiments were carried out under light-proof conditions. It can be observed that the system is in a homogeneous state at the reaction temperature. When the reaction is completed and the temperature approaches room temperature, the system is separated from the solid and liquid, and the composite material can be separated from the system. 0.1M HCl and 0.1M NaOH were used to adjust the system pH to 7. After the reaction, 1 ml of the system supernatant was filtered through a 0.22μm PTFE filter head and the removal rate measured by high performance liquid chromatography was 63%.

[0030] Example 2

[0031] First, add 20g MOF to the modifier solution, seal it with plastic wrap and pierce it with a needle to condense the steam and reflux. Then oscillate it in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min for 8h. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind to obtain the modified MOF for use. Dissolve 10g biomass in the modifier solution and stir it magnetically at room temperature for 12h. Then add the modified MOF and stir it at room temperature for 10h. Centrifuge the obtained mixed solution several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a petri dish, dry it at 80℃ to constant weight, grind it for use, and obtain the biomass-modified MOF composite. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, and then obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, and then mixed with metal chloride and added, and reacted at 90°C for 5 hours to obtain an ionic liquid with temperature control function. Soak MOF in deionized water for 24 hours and then centrifuge. Take 8g MOF and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. Then 10 g IL was added, finally forming a temperature-controlled and biomass-modified IL@MOF composite material.

[0032] Weigh 50mg of functionalized IL@MOF composite material and add it to 30ml, 50mg / L antiviral drug solution. Then, place the reaction system in a constant temperature shaker at 30℃ and 190rpm to fully promote the adsorption of antiviral drugs. Then, place the system at 80℃ for degradation reaction for 8h. All experiments were carried out under light-proof conditions. After the reaction, the composite material can be separated from the system by adjusting the reaction temperature. 0.1M HCl and 0.1M NaOH were used to adjust the system pH to 7. After the reaction, 1ml of the system supernatant was filtered through a 0.22μm PTFE filter head, and the removal rate measured by high-performance liquid chromatography was 92%.

[0033] Example 3

[0034] First, add 8g MOF to the modifier solution, seal it with plastic wrap and pierce it with a needle to condense the steam and reflux. Then oscillate it in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min for 8h. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind to obtain the modified MOF for use. Dissolve 10g biomass in the modifier solution and stir it magnetically at room temperature for 12h. Then add the modified MOF and stir it at room temperature for 10h. Centrifuge the obtained mixed solution several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a petri dish, dry it at 80℃ to constant weight, grind it for use, and obtain the MOF composite modified by biomass. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, and then obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, and then mixed with metal chloride and added, and reacted at 90°C for 5 hours to obtain an ionic liquid with temperature control function. Soak MOF in deionized water for 24 hours and then centrifuge. Take 8g MOF and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. Then 15 g IL was added to finally form a temperature-controlled and biomass-modified IL@MOF composite material.

[0035] Weigh 100 mg of functionalized IL@MOF composite material and add it to 50 ml, 60 mg / L antiviral drug solution. Then, place the reaction system in a constant temperature shaker at 30 ° C and 190 rpm to fully promote the adsorption of antiviral drugs. Then, place the system at 60 ° C for degradation reaction for 6 hours. After the reaction is completed, the composite material can be separated from the system by adjusting the temperature. 0.1M HCl and 0.1M NaOH are used to adjust the system pH to 7. After the reaction is completed, take 1 ml of the system supernatant and filter it through a 0.22μm PTFE filter head. The removal rate measured by high performance liquid chromatography is 79%.

[0036] Subsequently, an experiment on the removal of antiviral pollutants in actual wastewater was conducted: first, 100 ml of Haihe water was added to 50 mg / L of antiviral pollutants, the system was stirred evenly, and 50 mg of IL@MOF composite material was added. The system was then placed in an air bath oscillator at a constant temperature of 30°C and a speed of 190 rpm. After oscillation for 12 hours, the supernatant of the reaction system was taken for content analysis.

[0037] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to achieve the final preparation technology. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention. Matters not covered in the present invention belong to the known technology.

Claims

1. A modified IL-grafted MOF composite material proposed in the present invention is as follows: 1) First, add 1-10g MOF into the modifier solution, seal it with plastic wrap and poke holes with a needle to allow the steam to condense and reflux; 2) Oscillate in a constant temperature water bath at 50-150°C and an oscillation rate of 100-200 r / min for 1-12 hours. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind the modified MOF for later use. 3) Dissolve 1-100g of biomass in the modifier solution and stir magnetically at room temperature for 1-24h. Then add the modified MOF and stir at room temperature for 1-12h. Centrifuge the resulting mixture several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a culture dish, dry it at 60-80℃ to constant weight, grind it for later use, and obtain the biomass-modified MOF compound; 4) Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or a pyridine derivative or a quaternary ammonium salt derivative, react at a temperature range of 50-120° C. for 1-12 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, thereby obtaining compound 1; 5) Add compound 1 into water and dissolve it. Add a heteropolyacid aqueous solution containing an equimolar amount of compound 1 dropwise during stirring. After the addition is complete, raise the temperature to 60-100° C. at a heating rate of 1-10° C. per minute and react for 1-10 hours. Finally, filter out the solid precipitate and send it to a vacuum drying oven for drying to obtain compound 2; 6) Dissolve compound 2 in deionized water at 50-120° C., then mix it with metal chloride and add it, react at 90-120° C. for 1-6 hours to obtain an ionic liquid with temperature control function. 7) Soak the modified MOF in deionized water for 24 hours and then centrifuge. Take 1-10g MOF and mix it with NaCl solution, stir it for 24-48 hours, dialyze it in deionized water until it is chlorine-free, and then dry it at 80℃-100℃. Then add excess IL to finally form a temperature-controlled IL@MOF composite material.

2. The materials in step 1) include iron-based materials, chromium-based materials, cobalt-based materials and other materials based on various metals; the modified solution is an acidic aqueous solution such as hydrochloric acid and sulfuric acid, an alkaline aqueous solution such as ammonia water, and an oxidizing modifier such as hydrogen peroxide and ozone.

3. In the steps 1) and 3), the mass ratio of MOF to biomass is 1:1-1:

10.

4. In the step 4), the volume ratio of 1,3-propane sultone to toluene is 0.1-1:1; the amount of N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative added is 0.013 mol-0.065 mol.

5. In the step 6), the metal chloride is specifically AlCl3 or CrCl3; the molar ratio of the metal chloride to the compound 2 is 1:0.1-1.

6. In step 7), the mass ratio of MOF to NaCl solution is 1:1-1:20, and the molar ratio of MOF to IL is 1:1-1:

10.

7. A method for using the easily recyclable IL@MOF composite material prepared by the present invention in treating antiviral drugs in wastewater is as follows: The prepared material is added to wastewater containing antiviral drugs, and then the system is placed in a water bath oscillator and oscillated at a rate of 100r / min-500r / min to allow the pollutants to be fully adsorbed by the composite material. The system is then placed at 60℃-120℃ for 1-24h, and the supernatant is taken for content determination after the reaction. The prepared material can be recovered by external stimulation method.

8. The antiviral drug pollutants described are anti-HIV, anti-hepatitis, anti-influenza and anti-herpes virus, etc.

Citation Information

Patent Citations

  • Metal organic skeleton material as well as method for eliminating water organic medicine pollution

    CN107913673A